Local community impact-attitudes-actions toward China–Pakistan economic corridor development in Pakistan - Shahrukh Khan; Sehresh Hena; Inam Ullah Khalil; Muhammad Haseeb Raza; Li Hongwei; Kong Deji; Reda Abdelfattah Mohammad; Baoyu Cui (Frontiers in Human Dynamics)
IntroductionDevelopment initiatives can generate substantial economic, social, cultural, and environmental benefits for local communities, with their success largely contingent on residents’ perceptions, attitudes, and levels of support. Within the context of the China-Pakistan Economic Corridor (CPEC), local community perspectives particularly in Gilgit-Baltistan remain underexplored due to limited empirical data. This study aims to examine how CPEC development influences resident attitudes and to identify the factors that shape both passive and active forms of support.MethodsA total of 600 questionnaires were distributed over a two-month period, yielding 527 valid responses after excluding incomplete or invalid submissions (response rate: 85.83%). Structural Equation Modeling (SEM) was employed to analyze the complex interrelationships among perceived impacts, community attitudes, and supportive behaviors.ResultsPerceived economic and social benefits were found to positively influence residents’ attitudes toward CPEC, while environmental concerns had a negative impact. Overall, the local community expressed strong support for the development of CPEC. Furthermore, a significant positive association was observed between favorable attitudes and both passive and active support behaviors.DiscussionThese findings highlight the multifaceted nature of community responses to large-scale development projects. The study contributes theoretical insight into the determinants of local support and offers practical guidance for policymakers involved in CPEC. Maximizing socio-economic gains while actively mitigating environmental concerns is crucial. Importantly, incorporating community input into the planning and implementation process is essential for ensuring the sustainability and long-term success of CPEC initiatives.